A random finite set approach for tracking time-varying number of acoustic sources using a single acoustic vector sensor - Madhukumar, A. S. (2013)
Existing localization approaches developed using acoustic vector sensor (AVS) signals normally assume that the sources are static and the number of sources is known. In this paper, a novel approach is developed to estimate the 2-D direction of arrival (DOA) of an unknown and time-varying number of acoustic sources using a single AVS. A random finite set (RFS) is employed to characterize the randomness of the state process, i.e., the dynamics of source motion and the number of active sources. Also the measurement processes are modeled by RFS since we allow the AVS report undesired events by sending an empty set other than received signals under regular cases. We further employ particle filtering to approximate the posterior DOA distributions. The performance of the proposed approach is demonstrated by simulated experiments.